Community policing as a partnership between the police and the community: a european experience - Slipchenko, Tetyana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2022)
The article analyzes the concepts, philosophy, principles and basic forms of Community Policing as a model of interaction between the National Police of Ukraine and the population. A historical digression of the formation of the Community Policing strategy was made and it was proved that it was based on the implementation of the basic principles of modern police of Robert Peel, modified and tested in the law enforcement agencies of democracies. It is proposed to define Community Policing in the sense of a community-based approach to policing, which recognizes that effective policing depends on community assistance and support and is based on innovative collaboration between the police and the community to jointly identify and solve problems. facing the community. It has been proved that Community Policing, as a model of interaction between the police and the population, has its own philosophy and certain organizational principles. The purpose of realization of the Community Policing model is substantiated and defined and the expected results of its introduction in Ukraine are formulated. The most promising forms of interaction between the police and the population within the model are analyzed. Community Policing operating in Ukraine. The experience of European countries on the implementation of Community Policing and the possibility of its implementation in Ukraine is studied, the main legal acts regulating the functioning of the Community Policing model in Ukraine are analyzed.